Lightning simulation study on line surge arresters and protection design of simple structures - Jamoshid, Noor Shahida (2008)
There was a recent incidence where a direct lightning strike on the earth shielding conductor of a 275/132kV quadruple circuit transmission line had caused the breakage of the conductor at four points. Three short conductors connecting the line arrester installed on the 132kV line were not affected. The location of the affected arrester was not at the nearest tower to the point of strike but at the adjacent tower. The arresters at the nearest tower were not affected. This phenomenon was studied using ATP-EMTP simulation. Transmission tower is modeled according to the multi storey tower proposed by Masaru Ishii which was validated through theory and calculation. Simulation results show that the phenomenon cannot be conclusively reproduced within the ATP-EMTP simulation. Study indicating the fact that the phenomenon may be a one-off special case event. Overhead line is modeled by applying the PI subroutine file. This project also study the protection of simple structures from lightning strikes. The most common and simplest form of lightning protection is by using a vertical rod which has the function of intercepting a lightning stroke before it can strike a nearby object it is protecting, and then discharging the current to ground. In this simulation study, 1500 strokes were applied in a square plot ground area of 1kmÂ² and the number of flashes to ground per square kilometer per year (Ng) is 15 strokes/ kmÂ²/year. A Monte-Carlo technique is used to manipulate the statistical distribution of lightning strokes. The program is written in C-language using MATLAB simulation.